Restoration of mRNA Expression of Solute Carrier Proteins in Liver of Diet-Induced Obese Mice by Metformin - Le, Jiamei; Fu, Yi; Han, Qiuqin; Wei, Xindong; Ji, Houlin; Chen, Yifan; Wang, Qiuying; Pi, Peixian; Li, Jilei; Lin, Xinjie; Zhang, Xiaoying; Zhang, Yong; et al. (Frontiers in Endocrinology, 2021)
Metformin (MET), the most common medicine for type 2 diabetes (T2DM), improves insulin sensitivity by targeting the liver, intestine and other organs. Its impact on expression of the solute carrier (Slc) transporter genes have not been reported in the mechanism of insulin sensitization. In this study, we examined Slc gene expression in the liver and colon of diet-induced obese (DIO) mice treated by MET through transcriptomic analysis. There were 939 differentially expressed genes (DEGs) in the liver of DIO mice vs lean mice, which included 34 Slc genes. MET altered 489 DEGs in the liver of DIO mice, in which 23 were Slc genes. The expression of 20 MET-responsive Slc DEGs in the liver of DIO mice were confirmed by qRT-PCR, in which 15 Slc genes were definitely restored by MET, including Slc2a10, Slc2a13, Slc5a9, Slc6a14, Slc7a9, Slc9a2, Slc9a3, Slc13a2, Slc15a2, Slc26a3, Slc34a2, Slc37a1, Slc44a4, Slc51b and Slc52a3. While, there were only 97 DEGs in the colon of DIO mice with 5 Slc genes, whose expression was not restored by MET. The data suggest that more genes were altered in the liver over the colon by the high fat diet (HFD). Alteration in 20 Slc genes was confirmed in the liver of DIO mice and 15 of them were restored by MET in association with improvement of insulin sensitivity and obesity. The restoration may improve the uptake of glucose, amino acids, mannose, fructose, 1,5-anhydro-D-glucitol and bumetanide in hepatocytes of the liver of DIO mice. The study provides new insight into the mechanism of metformin action in insulin sensitization and obesity.